Islamic Consumer Behavior Theory - Sakinah Azzahra; Muslimin Kara (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
The development of modern lifestyles has given birth to different views on the purpose of consumption, where conventional economics places material satisfaction (utility) as the main orientation, while Islamic economics emphasizes the benefit and welfare of the world-hereafter (falah) as the goal of consumption. This research aims to analyze Islamic consumer behavior theory, its basic principles, factors that influence it, and its implementation in modern life. This research uses a qualitative approach with a descriptive-analytical method through a literature review of books, scientific journals, and relevant Islamic economic sources. The findings of the study show that Islamic consumer behavior is built on the principles of halal and thayyib, balance (wasathiyah), justice and utility, as well as the prohibition of israf and tabzir, so that consumption is not only seen as an economic activity, but also as a form of worship that has social and spiritual responsibility. In addition, religiosity, social environment, culture, economic conditions, and psychological factors have been proven to influence a Muslim's consumption patterns in the face of globalization and digitalization. The implications of this study show that the application of Islamic consumer behavior can be an alternative in building wiser, ethical, and sustainable consumption patterns, while strengthening the development of the Islamic economy in the midst of modern society.